NO EVIDENCE OF LYME DISEASE IN AUSTRALIA YET. (February 2015) - Stenos, John; Vincent, Gemma; Tadepalli, Mythili; Nguyen, Chelsea; Hussain, Hazizul; Islam, Aminul; Graves, Stephen
Abstract : Aims: To develop a screening protocol for detecting Lyme disease in Australia. Methods: A protocol for the serological screening of sera was established whereby the initial screen was performed by enzyme immunosorbent and immunofluorescence assay and if both assays were positive a confirmatory testing was performed by Western blot. Culture and qPCR assays were used to screen human blood and tick lysates. Results: All known Lyme disease positive sera obtained from Europe and the USA have been positive in all three assays confirming the ability of these assays to detect genuine cases of this disease. No Australian serum (in a non-traveller) has tested positive in all three assays suggesting that no person has been infected with a Borrelia spp. to date in Australia. Similarly, the testing of patient bloods by qPCR and culture have all been negative. Screening of Australian ticks for Borrelia spp. has yielded negative results, supporting the view that these ticks do not carry nor transmit Lyme disease. Discussion: While it is impossible to prove the absence of a Lyme disease in Australia and while keeping an open mind on this possibility, this data suggests that Lyme disease does not occur in Australia.